Sate Bandeng sebagai Simbol Pelestarian Wisata Kuliner Makanan Khas di Kota Serang Provinsi Banten - Eli Apud Saepudin; Parko Prahima; Dede Qodrat Alwajir; Arief Rachman; Sri Atomy (TOBA: Journal of Tourism, Hospitality, and Destination, 2024)
Culinary tourism in the province of Banten is very much like rabeg pecak bandeng, gemblog, grem asem, tempe pedot, soursop pickles, buffalo meat jerky, candied kolang-kaling, urab and many more but what is very phenomenal is milkfish satay is one of the specialties of Serang City where milkfish satay is very favored by both young and old the reason is this culinary one without thorns so it is easy to consume. Banten has a high historical and cultural value. Its existence is not only a delicious dish, but also a symbol of the preservation of culinary tourism and cultural identity of Serang City. Local and foreign tourists definitely buy milkfish satay souvenirs to take home. Milkfish satay is not only a delicious dish, but also an important symbol of preserving the culinary tourism and cultural identity of Serang City, Banten. Efforts to preserve and develop milkfish satay need to be carried out in a sustainable manner to ensure cultural preservation and increase the attractiveness of culinary tourism in Serang City. The research method used is descriptive qualitative with a literature study design. This research aims to find out the culinary tourism of milkfish satay in the city of Serang, a symbol of the typical food of Serang City which has a high taste that is loved by connoisseurs of culinary tourism in Serang City.